The Effect of the "Great Village" on Psychological Outcomes, Burden, and Mastery in African American Caregivers of Persons Living With Dementia. (October 2020) - Brewster, Glenna S.; Epps, Fayron; Dye, Clinton E.; Hepburn, Kenneth; Higgins, Melinda K.; Parker, Monica L.
The " Great Village, " a cultural adaptation of a psychoeducation intervention the " Savvy Caregiver " for African American caregivers of persons living with dementia (PLwD), aims to develop caregivers' skills and improve the quality of the lives of both the PLwD and their caregivers. The goal of this study was to determine the effectiveness of the Great Village on depressive symptoms, anxiety, burden, and mastery in African American caregivers ( N = 142). A three-arm randomized control trial ( Great Village, Great Village + exercise, and attention control) was conducted over a period of 6 months. Caregivers who received either Great Village or Great Village + exercise reported significant reduction in depressive symptoms and improvement in mastery. Caregivers who received only Great Village reported a reduction in anxiety. Receiving no intervention worsened caregiver burden. African American caregivers should receive culturally tailored interventions to support their health and well-being and improve their competence in caregiving.